2020
DOI: 10.1083/jcb.201910021
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulation provides specificity to biomolecular condensates in the cell cycle and cell polarity

Abstract: Biomolecular condensation is a way of organizing cytosol in which proteins and nucleic acids coassemble into compartments. In the multinucleate filamentous fungus Ashbya gossypii, the RNA-binding protein Whi3 regulates the cell cycle and cell polarity through forming macromolecular structures that behave like condensates. Whi3 has distinct spatial localizations and mRNA targets, making it a powerful model for how, when, and where specific identities are established for condensates. We identified residues on Wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…We first looked to see if the wbsm cells had altered cell cycle or polarity phenotypes. We found that these cells were more synchronous in their nuclear division cycles than control cells as assessed by scoring the cell cycle state of neighboring nuclei and comparing to what would be expected to be found by chance (Figure 1D) (Gerbich et al 2020). The wbsm cells had a synchrony index around 1.4, indicating a moderate phenotype that is less severe than what is seen in the whi3DpolyQ or the whi3D, which are around 1.7 and 1.9, respectively (Nair et al 2010;Lee et al 2015).…”
Section: Resultsmentioning
confidence: 67%
“…We first looked to see if the wbsm cells had altered cell cycle or polarity phenotypes. We found that these cells were more synchronous in their nuclear division cycles than control cells as assessed by scoring the cell cycle state of neighboring nuclei and comparing to what would be expected to be found by chance (Figure 1D) (Gerbich et al 2020). The wbsm cells had a synchrony index around 1.4, indicating a moderate phenotype that is less severe than what is seen in the whi3DpolyQ or the whi3D, which are around 1.7 and 1.9, respectively (Nair et al 2010;Lee et al 2015).…”
Section: Resultsmentioning
confidence: 67%
“…Some target RNAs of Whi3 are enriched in the vicinity of nuclei and at the cell cortex ( 36, 37 ), prompting us to hypothesize that that Whi3 condensates may be associated with the endoplasmic reticulum (ER), which is associated with both nuclei and the cortex. To test this, we created an Ashbya strain in which Whi3 was tagged endogenously with tdTomato ( 39 ) and a GFP-tagged ER marker, the translocon component Sec63, was expressed from a plasmid. Whi3 puncta in these cells appeared co-localized with diverse ER structures, including tubules and nuclear-associated ER (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms by which cells localize condensates and control their sizes have remained relatively unexplored. Whi3-RNA condensates function by positioning cell cycle and cell polarity signaling to distinct regions in the cell, indicating that condensate localization is intimately tied to function ( 12, 36-39 ). Our finding that Whi3 assemblies persistently associate with the ER suggests that attachment to endomembranes plays a key role in controlling condensate localization.…”
Section: Discussionmentioning
confidence: 99%
“…We note that phosphorylation of proteins with IDRs appears to inhibit their incorporation into biomolecular condensates through liquid-liquid phase separation both in vitro and in cells (Owen and Shewmaker, 2019), meaning that phosphorylation of Sts5 IDR may contribute to both Rad24-dependent and -independent forms of regulation. More generally, the connection between RNPs and cell polarity is an emerging theme that has been described in several organisms (Gerbich et al, 2020; Jansen et al, 2009; Lee et al, 2015, 2020). Our work supports a critical role for regulated assembly of P-bodies in the cell polarity program that establishes and maintains cell morphology.…”
Section: Discussionmentioning
confidence: 99%